The navigator : the log of John Anderson, VOC pilot-major, 1640-1643 - Anderson, John, active 17th century (European expansion and indigenous response ;, 2010)
Captain John Anderson served in the Dutch East India Company (VOC) as 'Pilot-Major' between 1640 and 1643. This was his fourth voyage to the Indies and the only one he chose to record. His log gives great insight into the subject of European travel in Asia in the Early Modern Period.